2005
DOI: 10.1200/jco.2005.01.198
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of Tamoxifen and Radiotherapy After Breast-Conserving Surgery in Early-Stage Breast Cancer

Abstract: The current analysis does not suggest an adverse effect on local or systemic control with CONC versus SEQ TAM and RT in node-negative breast cancer. A randomized trial is encouraged to validate these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(46 citation statements)
references
References 19 publications
1
40
0
5
Order By: Relevance
“…The clinical significance of concurrent tamoxifen therapy in radiotherapyrelated toxicity is controversial. Several reports have shown an increased risk of pulmonary and breast fibrosis after concurrent treatment with tamoxifen therapy and radiotherapy (18,19), whereas other reports did not show any risk (20). Furthermore, an in vitro experimental study showed that the radiosensitivity of hormone-dependent breast cancer cells might be reduced through the cytostatic effect of tamoxifen (21).…”
Section: Discussionmentioning
confidence: 94%
“…The clinical significance of concurrent tamoxifen therapy in radiotherapyrelated toxicity is controversial. Several reports have shown an increased risk of pulmonary and breast fibrosis after concurrent treatment with tamoxifen therapy and radiotherapy (18,19), whereas other reports did not show any risk (20). Furthermore, an in vitro experimental study showed that the radiosensitivity of hormone-dependent breast cancer cells might be reduced through the cytostatic effect of tamoxifen (21).…”
Section: Discussionmentioning
confidence: 94%
“…The authors, however, encourage a randomized trial to validate this finding. 26 Anastrozole is at least as effective as tamoxifen as preoperative therapy for postmenopausal women with breast cancer, and is more effective than tamoxifen in certain clinically relevant subgroups. Anastrozole represents an effective preoperative endocrine treatment option for postmenopausal patients with hormoneresponsive breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although some experimental data suggest that tamoxifen might decrease radiation sensitivity of breast cancer cells in vitro, clinical data do not substantiate this observation [63,64]. Moderately increased risks for late pulmonary damage and subcutaneous fibrosis have been reported at least for subsets of patients [65,66].…”
Section: Adjuvant Endocrine Treatmentmentioning
confidence: 85%